SECURITY STUDIES AND INTERNATIONAL TERRORISM - Erdag, Ramazan (European Scientific Journal, ESJ, 2013)
The realist school of international relations regards the international environment as anarchic. Sovereign states are perceived as being engaged in a struggle to maximize their individual interests. Therefore, the states’ chief priority is to counter threats from their adversaries so as to ensure the security of their citizens. In this context, the concept of security has traditionally been understood as an environment that is free of danger and threats. As International Relations IR theory has evolved, however, new approaches to the concept of security have been developed. New understandings of security have made the concept more multifaceted and visionary. This article firstly focuses on security studies field, in this regard and asks what can be done to combat global terrorism and how the conditions for peace and stability can be ensured? Given the rise of new global disputes and cultural perspectives, security can no longer be isolated venture; rather, it is a collective endeavor. In the contemporary era, greater international collaborations and broader alliances are needed to provide international security. This article discusses the effectiveness of such global alliances -especially NATO- in providing global security.